2000
DOI: 10.1067/mcp.2000.105151
|View full text |Cite
|
Sign up to set email alerts
|

The steady-state disposition of indinavir is not altered by the concomitant administration of clarithromycin

Abstract: The combination of indinavir sulfate and clarithromycin is generally well tolerated and can be coadministered without dose adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A study with a similar design found a clinically non-significant effect of CLR on indinavir, i.e. , indinavir C max increase of 58% and AUC of 47% in a smaller group of 12 patients at steady state [165]. Co-administering a darunavir/ritonavir combination with CLR in a randomized open-label cross-over study in 18 healthy volunteers resulted in a small increase of darunavir AUC by 13% and C max by 17% [166].…”
Section: Resultsmentioning
confidence: 99%
“…A study with a similar design found a clinically non-significant effect of CLR on indinavir, i.e. , indinavir C max increase of 58% and AUC of 47% in a smaller group of 12 patients at steady state [165]. Co-administering a darunavir/ritonavir combination with CLR in a randomized open-label cross-over study in 18 healthy volunteers resulted in a small increase of darunavir AUC by 13% and C max by 17% [166].…”
Section: Resultsmentioning
confidence: 99%
“…Several antiretroviral agents and other drugs coadministered in AIDS patients can pharmacokinetically act as inhibitors or inducers. However, coadministration of clarithromycin, an inhibitor of CYP3A4 with indinavir, did not alter the blood levels of indinavir (Boruchoff et al 2000). Administration of antiretrovirals concurrently with other therapeutic agents may lead to increased absorption as a result of inhibition of P-gpmediated efflux and CYP-mediated metabolism leading to potential toxicity.…”
Section: Integrated Functions Of Efflux and Metabolismmentioning
confidence: 87%
“…[17] Similar variations in the pharmacokinetics of clarithromycin have been reported when clarithromycin was administered in conjunction with other protease inhibitors, and these variations have had little effect upon clinical outcome. [36-38] Since it is unlikely that the observed changes in exposure will have clinical significance, no dose adjustment is required for darunavir or clarithromycin in patients with normal renal function. A 50% dose reduction is recommended for clarithromycin when coadministered with darunavir for individuals with creatinine clearance of 30–60 mL/min.…”
Section: Protease Inhibitorsmentioning
confidence: 99%